Numbness of the ear following inferior alveolar nerve block: the forgotten complication - Ngeow, Wei Cheong; Chai, W.L. (Nature Publishing Group, 2009)
This article presents a distant complication in the auricle following the administration of a standard inferior alveolar nerve block. The patient experienced profound numbness of the auricle on the ipsilateral side of the injection that lasted for about an hour following unintended injection to the auriculotemporal nerve.